Revitalisasi Nilai-nilai Budaya Nagekeo Melalui Dialohg Antar Generasi di Pulau Flores - Klemens Mere (Yayasan Riset dan Pengembangan Intelektual, 2025)
Intergenerational dialogue is increasingly recognized as a key pathway for sustaining local cultural values amid rapid social change. This literature review explores strategies for revitalizing Nagekeo cultural values in Flores through structured dialogue between elders and youth. Drawing on studies from 2020 onward, the review identifies that cultural revitalization becomes more meaningful when dialogue is grounded in living traditions—such as oral narratives, customary rituals, local language practices, and communal work ethics—while also allowing younger generations to reinterpret these values in contemporary forms. Effective intergenerational dialogue is not merely cultural transmission, but a reciprocal learning process that strengthens cultural identity, empathy, and social cohesion. The review also highlights persistent challenges, including weakening family-based cultural communication, the marginalization of local culture in formal education, and the influence of globalized lifestyles that may distance youth from local traditions. Overall, revitalization in Nagekeo requires sustainable partnerships among families, schools, traditional leaders, and cultural actors so that cultural values can remain relevant, lived, and adaptive in the daily lives of younger generations.